Mass Media and the Cultivation of Fear of Crime in Nigeria (Journal of Management and Social Sciences, 2017)
AbstractQuestions and concerns have been raised about the fear-generating potentials of mass media in Nigeria in the face of the rising rate of crime in the country. The public, it is argued, suffer from hysteria about crime fanned up by newspapers and television.Hence, the influence of the mass media in escalating crime for the purpose of impacting on public policies has continued to be the focal point of discussion by criminologists. This paper contributes to literature by expanding knowledge on the relationship between fear of crime and media consumption in Nigeria. The main objective of the paper is to examine the modifiers of the relationships between media and fear. The suitability of cultivation theory in accounting for the influence of the media on the social perception of fear in the country was also examined. The study draws on the literature of risk perception and risk communication, as well as secondary data on the aetiology of fear and public beliefs about crime in a survey of Criminal Victimisation and Safety conducted by CLEEN Foundation. It concludes that most Nigerians do not have scientific foundation for their belief about crime as they are often fed with information about crime from media sources that may not appreciate nor care about the (in)accuracy of that information and that may use crime to entertain sell, advertise, exploit, or win patronage. Given the ubiquity of messages about crime in our society and the costs of inaccurate information, the study proposes that criminal justice officials- the police and other security agents should provide the mass media and by extension, the public with reliable information about crime, including information about the risk of victimisation for different criminal offences.Â KeywordsCrime, cultivation theory, fear, risk, victimisation